Gold(I)-Catalyzed Intramolecular C(sp3)–H Bond Functionalization - Miguélez, Rubén; Arto, Omar; Rodríguez-Arias, Carlos; Barrio, Pablo (Synthesis, 2024)
The merger of two of the most rapidly growing fields in catalysis, namely gold-catalysis and C–H activation/functionalization has resulted in major breakthroughs, affording unprecedented transformations. This review covers the most relevant contributions in this field during the last 10 years, restricted to the intramolecular functionalization of C(sp3)–H bonds.1 Introduction2 Carbene/Vinylidene Insertion3 [1,5]-H Shift4 Gold-Stabilized Vinyl Cation Mediated5 Summary and Outlook
Keywords: gold-catalysis; C–H functionalization; cyclization; carbene insertion; [1,5]-hydride shift; vinyl cation